TANGGUNG JAWAB SEKUTU MAATSCHAP TERHADAP PIHAK KE 3 DALAM SUATU PERJANJIAN KONSORSIUM TERKAIT BUBARNYA MAATSCHAP ATAS KEHENDAK PARA SEKUTU (Kasus Perjanjian Konsorsium antara PT Agro Bintang Dharma Nusantara dengan Pemerintah Daerah Balikpapan, Bontang, K - Julius Caesar Transon Simorangkir (Universitas Lampung, 2015)
The development of society in the field of economy requires laws to regulate economic problems. Scientific developments in the field of economy should be accompanied by regulations that govern them. Dynamic human life resulted in a pattern of life that compound so that the interests of each individual is different, if not set or laid out by the law, there will be cheating in any transaction or trade activity. In the case of procurement of ferry quickly conducted a consortium of several regions in Borneo as Balikpapan, Bontang, Paser, and east Kutai PT Argo Stars Darma Nusantara in terms of cooperation agreements number 021/ABDN-Dir/SPK/X/01 dated October 4th, 2001, for the provision of services fast boats